Influence of Pulsed Reverse Electrodeposition on Mechanical Properties of Ni–W Alloys - Zeyu Gu; Jhen-Yang Wu; Yiming Jiang; Tomoyuki Kurioka; Chun-Yi Chen; Hwai-En Lin; Xun Luo; Daisuke Yamane; Masato Sone; Tso-Fu Mark Chang (Electrochem, 2024)
Ni–W alloys have received considerable interest as a promising structural material for microelectromechanical systems (MEMS) due to their exceptional properties, including hardness, ductility, corrosion resistance, and thermal stability. However, the electrodeposition of Ni–W alloys in the MEMS fabrication process to achieve intact structures with a thickness of several tens of micrometers is challenging due to the occurrence of cracking caused by side reactions and internal stresses during the electrodeposition process. To address this issue, our focus was on pulsed reverse electrodeposition (PRE) as a potential solution. The utilization of the PRE technique allows for a high concentration of reactive species on the electrode surface, thereby mitigating side reactions such as hydrogen generation. In this study, we examined the effects of the PRE method on the morphological characteristics, average crystal grain size, Vickers hardness, and micro-mechanical properties of Ni–W alloys.